Aplikasi Pemberian Tinggi Genangan dan Dosis Pupuk Organik terhadap Hasil Padi Varietas Ciherang - SIMAMORA, GEBY SAHALA; DHARMA, I PUTU; ADNYANA, GEDE MENAKA (Agrotrop : Journal on Agriculture Science; Vol 8 No 2 (2018)DO - 10.24843/AJoAS.2018.v08.i02.p05, 2019)
The Application of High Puddle and Organic Fertilizer on Rice Yield Ciherang Variety . Rice ( Oryza sativa L.) is the staple vital food of Indonesian people. National rice production has not been able to meet the needs of the population, despite many efforts such as the use of improved varieties, fertilization, the use of agricultural machinery, and the use of pesticides. This study aimed to determine the effect of water level and organic fertilizers on crop yields of rice. This experiment used randomized block design in a simple treatment, namely the combination of the water level and the dose of organic fertilizer. This research using analysis of variance (ANOVA) to determine the effect of treatment on the variables tested. If treatment significant it will be followed by LSD test 5%. The results showed that the treatment of combination of water level and organic fertilizers provide a very real effect on the growth and yield of rice (Harvest dry grain yield ha -1 ). Harvest dry grain yield ha -1 obtained at the highest AMP2 treatment, namely without flooding water and organic fertilizers and 6 t ha -1 at 10.92 t ha -1 were significantly higher 70.09 % compared to the treatment of farmers. Based on the research results, it can be recommended that the application of water-saving cultivation of organic fertilizer with a dose of 6 t ha -1 needs to be done to improve rice yields.